Creation of an electronic trilingual dictionary of biological terms with linguoculturological components - Taisiya Maryshkina, Anna Kalizhanova; Ishmuratova, Margarita; Gruzina, Yelena; Ibrayeva, Bayan (Opción, 2020)
Digitization of educational system of the Republic of Kazakhstan, coupled with the Trilingualism program, has revealed the problem of the lack of trilingual training and resource books and, as a result, their mass creation in electronic form. This article deals with the experience of creating a disk version of an electronic trilingual dictionary of biological terms with a linguoculturological component using the Adobe Dreamweaver program. The experience of application and use based on a survey of teachers suggests that Adobe Dreamweaver is ideal for visualizing the linguoculturological component of the term in order to effectively memorize the latter